Phytoalexins: Current Progress and Future Prospects (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
Phytoalexins are antimicrobial substances of low molecular weight produced by plants in response to infection or stress, which form part of their active defense mechanisms. It is now clear that phytoalexins exhibit toxicity across much of the biological spectrum, prokaryotic and eukaryotic. Starting in the 1950s, research on phytoalexins has begun with biochemistry and bio-organic chemistry, resulting in the determination of their structure, their biological activity as well as mechanisms of their synthesis and their catabolism by microorganisms. Elucidation of the biosynthesis of numerous phytoalexins has also permitted the use of molecular biology tools for the exploration of the genes encoding enzymes of their synthesis pathways and their regulators. This has led to potential applications for increasing plant resistance to diseases. Phytoalexins display an enormous diversity belonging to various chemical families such as isoflavones, isoflavanones, pterocarpans, isoflavans, flavanones, coumestans, furanoacetylenes, phenylpropanoids, steroid glycoalkaloids, norsesquiterpenoids/sesquiterpenoids, coumarins, diterpenes, ent-kaurane-related diterpenoids, acidic sesquiterpenoids, 3-deoxyanthocyanidins, naphthaldehydes, indoles and stilbenes. Research papers dealing with all aspects of phytoalexins, including structure elucidation; chemical synthesis; methods for phytoalexin analysis in plant extracts or biological fluids; biosynthesis studies including modulation of phytoalexin synthesis; engineering of phytoalexin biochemical pathways in plants and microbes; biological activities; structure/activity relationships; phytoalexin metabolism in planta and by micro-organisms; roles and ATP Binding Cassette (ABC) transporters or Multi-Drugs Efflux (MDE) transporters are welcome for inclusion in this Special Issue of Molecules. Review articles, particularly those dealing with the themes mentioned above are also particularly welcome for inclusion.